PENGARUH WORK-LIFE BALANCE, BEBAN KERJA, DAN STRES KERJA TERHADAP EMPLOYEE ENGAGEMENT - Supriatna, Dadar; Latifah, Latifah; Karyadi, Haris; Widyastuti, Widyastuti; Tahalele, Olivia (JURNAL LENTERA BISNIS, 2025)
In the era of increasingly rapid globalization and digitalization, the dynamics of the world of work are experiencing significant changes. Companies are required to not only focus on productivity, but also on employee welfare. The purpose of this research is to determine the influence of work-life balance, workload, and work stress on Employee Engagement. This research uses a quantitative type of research. Data collection in this research was carried out using two main techniques, namely primary and secondary data. And the population obtained in this study was 150 respondents. The analysis technique in this research uses Multiple Linear Regression with SPSS software.  The research results found that work-life balance, workload, and work stress influence employee engagement.